Hamlet Turn'd Turke: Shakespearean Postcolonialities - Lupić, Ivan (Array, 2009)
The chapter uses a recent Bosnian production of Shakespeare’s Hamlet, where the play is set at the Ottoman court, in order to reflect on the larger issues this kind of cultural intervention attempts to engage. The production is first considered in terms of the historical contexts it explicitly invokes or alludes to, which relate to the Ottoman court on the one hand and to the relationship between the Ottoman empire and the Christian West on the other. Addressing the politics behind this theatrical event, the chapter then sets it against the backdrop of recent discussions of the Turk in English early modern drama, thus attempting to convey some sense of the breadth of the issues raised and to articulate the concerns which are of specific interest to the literary scholar. Attention is paid to the text/s of Shakespeare’s Hamlet as well as to what might be envisaged as alternative yet less literal responses to the same cultural problem. The general aim of the discussion is to draw attention to the specific ways in which postcolonial Shakespeares function in the borderlands of Europe.